A Comparison Study of Cognitive and Neuropsychiatric Features of Essential Tremor and Parkinson's Disease. (15th December 2016) - Puertas-Martín, Verónica; Villarejo-Galende, Alberto; Fernández-Guinea, Sara; Romero, Juan Pablo; Louis, Elan D.; Benito-León, Julián
Background: Essential tremor (ET) and Parkinson's disease (PD) are two of the most common movement disorders. Leaving aside their motor features, these two conditions share several non-motor features, including cognitive dysfunction and personality changes. However, there are few data comparing the cognitive and personality profiles of ET with PD. Here we compare the cognitive and personality profiles of the two diseases. Methods: Thirty-two consecutive non-demented ET patients (13 females and 19 males) (67.7±9.8 years), 32 non-demented PD patients (13 females and 19 males) (67.7±9.5 years), and 32 healthy matched controls (14 females and 18 males) (67.9±10.1 years) underwent a neuropsychological test battery, including a global cognitive assessment and tests of attention, executive function, memory, language, and visuospatial function, as well as the Personality Assessment Inventory. Multivariable linear regression analyses were performed, adjusted for age, sex, years of education, medications that potentially affect cognitive function, number of medications, and the 17-item Hamilton Depression Rating Scale Total Score. Results: Neuropsychological scores were similar in PD and ET patients, but patients with disease performed more poorly than control subjects in cognitive tasks such as attention, executive function, memory, and naming. Discussion: ET and PD exhibited similar deficits in specific aspects of neuropsychological functioning, particularly those thought to rely on the integrity of the prefrontal cortex, and this suggests involvement of frontocerebellar circuits. These findings further challenge the traditional view of ET as a benign and monosymptomatic disorder.